Parkinson disease - Fahn, Stanley (Henry Stewart Talks, 2007)
Clinical symptoms of PD, Current knowledge on pathological mechanisms, Epidemiological facts, Genetic factors, Clinical management and DA replacement therapy, Importance of nonmotor symptoms, Future treatment directions